Detection of manipulations on printed images to address crime scene analysis: A case study. (June 2015) - Amerini, Irene; Caldelli, Roberto; Del Bimbo, Alberto; Di Fuccia, Andrea; Rizzo, Anna Paola; Saravo, Luigi
Highlights: We show a mock scene reproducing a cold case. Some crime scene images have been fraudulently manipulated. We were able to detect and localize the alteration on the printed image. We used an image forensic tool: the CADET (Cloned Area DETector). The image forensic analysis has given support to police investigation. Abstract: Photographic documents both in digital and in printed format plays a fundamental role in crime scene analysis. Photos are crucial to reconstruct what happened and also to freeze the fact scenario with all the different present objects and evidences. Consequently, it is immediate to comprehend the paramount importance of the assessment of the authenticity of such images, to avoid that a possible malicious counterfeiting leads to a wrong evaluation of the circumstance. In this paper, a case study in which some printed photos, brought as documental evidences of a familiar murder, had been fraudulently modified to bias the final judgement is presented. In particular, the usage of CADET image forensic tool, to verify printed photos integrity, is introduced and discussed.